2010
DOI: 10.2190/pm.40.1.c
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Maturation and Psychiatric Morbidity among Persons with Sickle Cell Anaemia in a Nigerian Teaching Hospital

Abstract: It is concluded that SCA subjects had significantly delayed sexual maturation and increased risk of psychiatric morbidity when compared to controls. The need for genetic counseling to reduce the prevalence of SCA was emphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Although most of its use was among primary care and general population subjects, it has also been found useful also in screening other special groups for psychiatric morbidity. 31,32 The GHQ-12 has been found to be a reliable screening tool in this environment. 32,33,34 Scores of 2 and above on the GHQ 12 were suggestive of psychiatric morbidity.…”
Section: Burden Of Care (Boc) Schedulementioning
confidence: 99%
See 1 more Smart Citation
“…Although most of its use was among primary care and general population subjects, it has also been found useful also in screening other special groups for psychiatric morbidity. 31,32 The GHQ-12 has been found to be a reliable screening tool in this environment. 32,33,34 Scores of 2 and above on the GHQ 12 were suggestive of psychiatric morbidity.…”
Section: Burden Of Care (Boc) Schedulementioning
confidence: 99%
“…31 One is hopeful that the creation and use of locally based family support organizations may also be useful in the care of these relatives.…”
Section: Psychological Experiences In Care Givingmentioning
confidence: 99%
“…SCD was also associated with delayed puberty. [28,51] Three studies from Nigeria reported the presence of overweight and obesity among patients with SCD although in lower proportions (an average of less than 3% of the sample population) [34,46,52].…”
Section: Resultsmentioning
confidence: 99%
“…[23,24,26] SCD was also associated with delayed puberty. [26,47] Three studies from Nigeria reported the presence of overweight and obesity among patients with SCD although in lower proportions (an average of less than 3% of the sample population). [30,42,48] Descriptive studies of macro-or micronutrient levels.…”
Section: Resultsmentioning
confidence: 99%